Implementasi Standar Usaha Pondok Wisata di Desa Wisata Pentingsari, Yogyakarta - I Wayan Sudarmayasa; M. Fauzan Noor; Eman Sukmana; Sabalius Uhai (Magister Tourism Study, Faculty of Tourism, Udayana University, 2020)
This article contains the implementation of the Minister of Tourism and Creative Economy (Permenparekraf) Regulation No. 9 of 2014 concerning homestay tourism standards in the management of homestay in pentingsari tourism villages as supporting the existence of tourist attractions in pentingsari tourism villages. The method used in this research is descriptive, namely by collecting data using questionnaires, field observations, literature studies, documentation and interviews with several key informants as resource persons such as chairperson, manager, and owner of the tourist cottage it self. This article describes the suitability of tourist huts in pentingsari tourism village in accordance with Permenparekraf No. 9 of 2014 from three priority aspects, namely management aspects, service aspects and product aspects, which is still not in accordance with the homestay conditions at the pentingsari village. Keywords: Implementation, Standards, Homestay, Tourism Village